College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.8 - One-to-One Functions and their Inverses - 2.8 Exercises: 66

Answer

$f^{-1}(x) = \sqrt[5] {\sqrt[7] y + 6 }$

Work Step by Step

$f(x) = (x^{5} - 6)^{7}$ $y = (x^{5} - 6)^{7}$ $\sqrt[7] y = x^{5} - 6$ $\sqrt[7] y + 6 = x^{5}$ $\sqrt[5] {\sqrt[7] y + 6 } = x$ $\sqrt[5] {\sqrt[7] y + 6 } = f^{-1}(x)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.